2022
DOI: 10.3389/fimmu.2022.969509
|View full text |Cite
|
Sign up to set email alerts
|

Combined proteomics and single cell RNA-sequencing analysis to identify biomarkers of disease diagnosis and disease exacerbation for systemic lupus erythematosus

Abstract: IntroductionSystemic lupus erythematosus (SLE) is a chronic autoimmune disease for which there is no cure. Effective diagnosis and precise assessment of disease exacerbation remains a major challenge.MethodsWe performed peripheral blood mononuclear cell (PBMC) proteomics of a discovery cohort, including patients with active SLE and inactive SLE, patients with rheumatoid arthritis (RA), and healthy controls (HC). Then, we performed a machine learning pipeline to identify biomarker combinations. The biomarker co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 65 publications
(67 reference statements)
1
12
0
Order By: Relevance
“…Elevated mitochondria-related gene expression suggests cell metabolism's role in aHUS clinical course, warranting further investigation. Notably, these gene expression patterns were not observed in other autoimmune diseases like systemic lupus erythematosus [20][21][22][23] or immunoglobulin G4-related disease [24], highlighting the unique immune cell profile in aHUS.…”
Section: Discussionmentioning
confidence: 91%
“…Elevated mitochondria-related gene expression suggests cell metabolism's role in aHUS clinical course, warranting further investigation. Notably, these gene expression patterns were not observed in other autoimmune diseases like systemic lupus erythematosus [20][21][22][23] or immunoglobulin G4-related disease [24], highlighting the unique immune cell profile in aHUS.…”
Section: Discussionmentioning
confidence: 91%
“…Silencing of CMPK2 in macrophages results in augmented ROS and perturbation of mitochondrial structure, leading to the upregulation of pro-inflammatory genes IL1β, TNFα, and IL8 ( Arumugam et al, 2022 ). Studies have reported a significantly increase of CMPK2 expression in active SLE compared to healthy individuals and inactive SLE patients, making it a promising biomarker for diagnosis and evaluation of SLE activity ( Xu et al, 2008 ; Li et al, 2022 ). Leucine aminopeptidase 3 (LAP3), encoded by the LAP3 gene, exhibits dual subcellular localization in both the cytosol and mitochondria ( Sickmann et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…ML models have been extensively explored for diagnosing SLE, defining clinical phenotypes, determining outcomes, and informing therapeutic decisions [ 23 ]. Previous studies utilizing ML to facilitate SLE diagnosis have employed diverse input data, including EHRs, genetic biomarkers, proteomics, lipidomes, or a combination of these data types [ 23 , 24 , 27 – 32 ]. This study is the first to incorporate genome-wide SNPs, PRS, and EHRs in an ML analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This study is the first to incorporate genome-wide SNPs, PRS, and EHRs in an ML analysis. Moreover, ML algorithms for diagnostic purposes in previous studies included RF, LASSO, SVM, LR, XGB, and Partial Least Square [ 23 , 24 , 27 – 32 ]. This study is the first to attempt to compare the diagnostic accuracy among six ML models.…”
Section: Discussionmentioning
confidence: 99%